Entrepreneurial Orientation and Innovation in Micro-Enterprises East Jakarta Culinary Sector (Journal of Entrepreneurship, Management and Industry (JEMI), 2022)
Micro-enterprises in the culinary sector are the most vulnerable sector to being affected by Pandemic COVID-19. One of the ways to improve the performance of micro-enterprises in the culinary sector is by improving entrepreneurial orientation skills and always innovating. This study aims to analyze the level of entrepreneurial orientation and innovation on the performance of micro-enterprises in the culinary sector in East Jakarta during the current pandemic. This study examined the effect of entrepreneurial orientation and innovation on the performance of micro-enterprises in the culinary sector in East Jakarta. This study uses the Probability Sampling technique with the Random Sampling method to analyze 44 micro-enterprises in the culinary sector in East Jakarta who have been in business for two years or more. The results indicate that partially entrepreneurial orientation had an effect on the performance of micro-enterprises in the culinary sector in East Jakarta, while innovation partially had no effect on the performance of micro-enterprises in the culinary sector in East Jakarta, but based on the F test, entrepreneurial orientation and innovation simultaneously affected the performance of micro-enterprises in culinary sector in East Jakarta.